A staggered coupling strategy for the finite element analysis of warm deep drawing process - Martins, J. M. P. (2016)
The thermomechanical finite element analysis of warm forming processes enables an improved comprehension of the process parameters affecting the material formability. However, the thermal and mechanical coupling problem is still a challenge from the computational standpoint. A staggered strategy for the thermomechanical coupling problem is presented in this study, which is based on an isothermal split approach and allows the treatment of the two problems separately. The exchange of information between the mechanical and the thermal problem is performed to achieve a compromise between computational cost and accuracy. The proposed algorithm was implemented in DD3IMP in-house finite element code. Its performance is analysed and compared with a classical strategy commonly employed for solving thermomechanical problems.